2016
DOI: 10.1128/aac.02586-15
|View full text |Cite
|
Sign up to set email alerts
|

Global Urine Metabolomics in Patients Treated with First-Line Tuberculosis Drugs and Identification of a Novel Metabolite of Ethambutol

Abstract: Population level variation of drug metabolism phenotype (DMP) has great implications in treatment outcome, drug-related side effects, and resistance development. In this study, we used a gas chromatography-time of flight-mass spectrometry (GC-TOF-MS)-based untargeted urine metabolomics approach to understand the DMP of a tuberculosis (TB) patient cohort (n ‫؍‬ 20) from Tripura, a state in the northeastern part of India. Urine samples collected at different postdose time points (2 h, 6 h, 12 h, 24 h, 36 h, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 37 publications
2
13
1
Order By: Relevance
“…Metabolites originating directly from the ingested TB drugs PZA, and one of its major metabolites, pyrazinoic acid (POA), formed through the de-amination of the parent drug (Ramappa and Aithal, 2013) and excreted through the kidneys (Saukkonen et al, 2006), were identified as significant markers and remained elevated throughout the first 4 weeks of therapy (Table 1), confirming observations made by Das et al (2016). PZA is a sterilizing drug that inhibits actively growing M. tuberculosis after being converted to its active form, POA, through the bacterial enzyme, pyrazinamidase.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Metabolites originating directly from the ingested TB drugs PZA, and one of its major metabolites, pyrazinoic acid (POA), formed through the de-amination of the parent drug (Ramappa and Aithal, 2013) and excreted through the kidneys (Saukkonen et al, 2006), were identified as significant markers and remained elevated throughout the first 4 weeks of therapy (Table 1), confirming observations made by Das et al (2016). PZA is a sterilizing drug that inhibits actively growing M. tuberculosis after being converted to its active form, POA, through the bacterial enzyme, pyrazinamidase.…”
Section: Discussionsupporting
confidence: 75%
“…This observed trend was further investigated in a follow-up study by specifically exploring the known urinary metabolites of INH, RIF, PZA, and EMB, and how the concentrations of these drug metabolites changed over time. A novel drug metabolite of EMB was identified with this approach (Das et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier reported methods were used in extracting urine analytes and subsequent derivatization. 23 An attempt was made to optimize methods to acquire data using commonly available quadrupole GC-MS in place of a multidimensional GC-MS. We observed that 100 ng of ribitol, as a spike-in standard, provides enough signal in urine metabolite analysis (Figure 2A, Figure S1). From the different GC-MS methods used for data acquisition (GC1-GC6), GC1 (50 °C for 1 min, ramp at 10 °C/min to 150 °C, hold for 3 min, ramp at 7 °C/ min to 300 °C and hold for 3 min) yielded maximum urine analyte details (Figure 2B, 2C, Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…In one example, computer-aided design of molecules that would "dock" onto the nsP2 protein and serve as protease inhibitors was performed. These designer molecules were synthesized and evaluated for their ability to inhibit protein activity (104). Several of these unnamed compounds, all having common core structures, were shown to inhibit nsP2 functionality in vitro, demonstrating the potential utility of targeted designer molecules based on in silico characteristics.…”
Section: Synthesis Of Designer Compoundsmentioning
confidence: 99%